CYTOGENETIC ACTIVITY STUDIES ON SOME MANGROVES OF KRISHNA–GODAVARI ESTUARY - T.BHASKARA RAO,; B.VENKATESWARA RAO,; K.RAMANJANEYULU, (International Journal of Pharma and Bio Sciences, 2014)
In the present study the bark of Ceriops decandra, collected from godavari estuary, Ceriops tagal and Xylocapus molluccensis collected from Krishna estuary of hexane, methylene chloride and methanol extracts were evaluated for Genotoxicity and cytotoxicity effects. The results indicated that the extracts from the all the three mangrove plant species have cyto-toxicity and it is substantiated from mitotic index and cell proliferation kinetics values. Further, the extracts indicated that they are geno-toxic and it is substantiated by an increase in sister chromosome exchange frequency.